Distribution, abundance and age ratios of Wrangel Island Lesser Snow Geese Answer caerulescens during autumn migration on the Yukon-Kuskokwim Delta, Alaska - Ely, C R; Takekawa, J Y; Wege, M L (Wildfowl, 1993)
We monitored the distribution, abundance, and productivity of Lesser Snow Geese on the Yukon-Kuskokwim (Y-K) Delta, Alaska during September and October 1991, when the geese were en route from their nesting grounds on Wrangel Island, Russia to wintering areas along the Pacific Coast. Adult geese in brood flocks were captured on Wrangel Island and fitted with either satellite platform transmitting terminal (PTT) transmitters (29 birds) or conventional very high frequency (VHF) radio transmitters (68 birds). All geese with active PTTs used the Y-K Delta. Geese marked with PTTs and VHF transmitters were first detected on the Y-K Delta on 19 and 25 September, respectively, and stayed 8-9 days (range 1 to 25 days) Geese with PTTs used the same areas as unmarked geese and geese with VHF radios, except for the south Delta where only satellite data were obtained. Flocks averaged 1122 birds, and did not vary significantly in size during the study. Population estimates from two independent methods ranged from 58,000 to 88,000 geese during October. Productivity of the Wrangel Island population, as determined from the proportion of young in flocks using the Y-K Delta, has varied from 0.5 to 42.1% with a mean of 29%, since 1975. Age-ratio estimates from the Y-K Delta were highly correlated with, and not significantly different from, those from autumn staging and wintering areas further south, which may indicate that immatures in this population of geese suffer little mortality during the second half of their autumn migration.